Pragmatics Principles of English Teachers in Islamic Elementary School - Pasaribu, Gumarpi Rahis; Daulay, Sholihatul Hamidah; Nasution, Putra Thoip (State institute of islamic studies salatiga, 2022)
This qualitative study presents the research results on Pragmatics politeness in the language of English teachers in Islamic elementary schools. The problem formulation of this research focuses on what and how Pragmatics politeness is in the language of English teachers in Islamic elementary schools. The objectives of this study are (i) to describe the form of Pragmatics speech in the language of English teachers; (ii) to describe the tools used in using Pragmatics politeness in the teacher's language, English. The research approach used is qualitative research. Data were collected from various communication events in teaching English in the classroom between teachers and students by participating in observation techniques, note-taking/recording techniques, and interviews. Structurally, the various sub-illocutions were delivered with one core speech unit alone or with a combination of core speech (TI) and supporting speech units (TD) in the form of asking questions, commanding acts, and opening speech units (TB) in the form of greetings. Pragmatics politeness speech acts of English teachers and students are generally expressed in imperative sentences (active and passive), declarative sentences, and interrogative sentences. Second, the tools of Pragmatics politeness in the language of English teachers in Islamic elementary schools found in the speech of the teaching process can function as an action stimulator, a request for approval of the action, an invitation.Keywords: Politeness, Pragmatics, Islamic elementary school.